(untitled) (Hekima Review, 2016)
This article explores experiences of working couples as they balance work and bring up children. It further points out the crucial role of house-helps in raising children and the challenges it poses. The research used exploratory qualitative design targeting working couples. Data was collected through Small Christian Community and Face-book platform. The study found out that more and more couples spend less time with their children leaving them under the care of house-helps who often are not trained in child development. The implication of the research is that policy makers need to design appropriate programs in building capacity for house-helps, policies for bene beneficial work environment for raising children and programs that would help families to balance work and family